We will not be silent : the White Rose student resistance movement that defied Adolf Hitler - Freedman, Russell (Clarion Books, 2016)
"The true story of the White Rose, a group of students in Nazi Germany who were active undercover agents of the resistance movement against Hitler and his regime"--Provided by publisher.